(untitled) (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study was to investigate the moderated mediation effect of teacher relations on the mediating effect of stress on the relationship between domestic abuse experience and depression in adolescents. Method/Statistical Analysis: To this end, approximately 860 middle and high school students from D city in Korea participated in the study survey. Collected data were analyzed using mean comparison analysis, reliability analysis, correlation analysis, and moderated mediation effect analysis. Findings: First, as a result of the difference test of depression according to general characteristics, there were significant differences according to gender, school grade, income level, and parent-teacher relationship. Second, as a result of the correlation analysis, there was a positive correlation between domestic abuse experience, stress, and depression, However, the teacher relationship negatively correlated with other variables. Third, stress was found to mediate between domestic abuse experience and depression. Fourth, teacher relationship was found to control between stress and depression. Fifth, teacher relations showed moderated mediation effects, on mediating effects of stress in the relationship between domestic abuse experience and depression. Improvements/Applications: Based on these findings, we discuss approaches to alleviating stress and reducing depression caused by domestic abuse experience